Design Of Web-Based Cash Flow Information System for Cash Receipts and Expenditures: Case Study on Sinar Jaya Paint Workshop Company - Putriyanti, Selvi; Amijaya, Hasanah Tisna; Ramlan; Isbandi (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
Sinar Jaya Paint Shop is a retail establishment that offers a diverse range of Duco paint products, including automotive paint, motorcycle paint, thinner, putty, jump on, and other related supplies. The shop owner must document all financial transactions, both incoming and outgoing. Sinar Jaya Paint Shop employs manual recording methods by documenting entries in a ledger, resulting in prolonged durations for both calculations and reporting. Consequently, the researcher intends to develop a web-based cash flow information system for cash receipts and disbursements at Sinar Jaya Paint Shop. The researcher employed a descriptive methodology in this investigation. This descriptive approach is categorized into three methods: the observational method, the literature review method, and the interview method. This study employs the Rational Unified Process (RUP) as its system development methodology. RUP is an iterative software development process framework established by Rational Software, a part of IBM, in 2003. RUP is a software development methodology for object-oriented models.